George Kennan on the Spanish-American War A Critical Edition of "Cuba and the Cubans" (Springer International Publishing, 2018)
This book presents a critical edition of the lecture "Cuba and the Cubans" by George Kennan the Elder, with a wide-ranging introduction examining its influence on American public opinion of the Spanish-American War. A well-known journalist and travel writer, George Kennan went to Cuba in 1898 to report on the war and conditions on the island for American readers. After the war, he delivered his lecture "Cuba and the Cubans" to audiences across the United States, depicting a backwards, inferior culture unprepared for independence. Frank Jacob's introduction offers rich context for his life, lecture, and influence, arguing that he contributed to the shift in public perception of Cuba from respected ally to wayward neighbor in need of American intervention. This critical edition illuminates the interaction between journalism, public opinion, and U.S. foreign policy at a key moment in the U.S.-Cuban relationship that still reverberates today.